Values Inculcation in Physical Education Courses: A Students’ and Teachers’ Perspective - Bulaklak, Edna M. (The journal of contemporary issues in business and government, 2021)
Teaching about values affects the way teachers think and consequently influence the way they behave, which is manifested in actions. Teachers are not neutral with regard to values, as values are embedded within their attitudes and exhibited through their behavior. The inclusion of Physical Education (PE) as a subject area in all schools regardless of levels is mandated in Article XIV, Section 19 of the 1987 Philippine Constitution. This qualitative study purported to determine the role of Physical Education teachers in the inculcation of values among college students. Twelve physical education teachers and eighty physical education students in the university have been chosen using criterion sampling. The findings revealed that the strength of the Physical Education teachers depended on how they perform their roles in instilling values among their students. They thread on being a model, a counselor, and a public relation specialist. But they needed to strengthen further their role of being a facilitator and a mentor. It is also important to enhance the skills of the teachers in assessing their student’s value system.